TO THE PERSONALITIES OF THE UKRAINIAN ASTRONOMY: SCIENTIFIC WORK OF KOSTYANTYN SAVCHENKO - Balyshev, M.; Vavilova, I. B. (Одеські астрономічні публікації, 2020)
The research is devoted to the study of the life and work of the outstanding Ukrainian astronomer-the- oretician Kostyantyn Savchenko (1910–1956), who worked in the field of celestial mechanics and dynamic cos- mogony at the Kharkiv and Odesa astronomical observato- ries in 1930–1950 years. As a result of historio-graphic analysis, we found that till now there is no comprehensive study of his scientific biography besides several publica- tions related to certain facts of his life and activity, mostly in the Odesa period, including the reminiscences by Prof. V.K.Abalakin. Despite this, the vast majority of aspects of the scientist’s life, including his scientific and teaching ac- tivity in the Kharkiv period in 1930s, remains unexplored. The astronomer's scientific work was devoted to the study of the motion and rotation of celestial bodies with variable masses, the exploration of the perturbations of the planets by geometry methods, research of the physical nature of gravity, and the development of cosmogonic theories. We consistently describe the life and activity of Prof. K.N.Savchenko at the Kharkiv and Odesa astronomical observatories, the scientific and teaching work at the Kharkiv State University, the Kherson State Pedagogical Institute, and the Odesa State University, analyzing the archive documents and his scientific publications